COMMODITY AND CUSTOMS ASPECTS OF THE FORMATION OF THE FRESH FLOWER MARKET - DONTSOVA, Inna; LEBEDYNETS, Vira; SAPOZHNYK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the issues of the flower business, which is among the top five types of entrepreneurial activity in the world. It is emphasized that more than 50 % of the value of imports of all floral products to Ukraine are freshly cut flowers for bouquets and interior decoration. The Netherlands is the undisputed leader in the import of flowers to Ukraine. Every year, we import more than UAH 93 million worth of flowers from this country. The main types of cut flowers supplied to Ukraine are roses, carnations, chrysanthemums, tulips, daffodils, lilies, gerberas, anthuriums and orchids. The article shows that today there are a number of unresolved issues related to customs control and customs clearance of imported floral products upon their importation into the customs territory of Ukraine, in particular, those related to ignoring the commodity principles of quality formation and procedures for identification of commercial products. The purpose of the study was to examine the commodity and customs aspects of the formation of the market for fresh (cut) flowers in Ukraine. A number of reasons have been identified why domestic production is valued much lower than imported ones: non-compliance with modern technologies (many growers grow flowers in greenhouses using the old methodology and end up supplying flower shops with cheap, low-quality goods); imported planting material (powerful producers adhere to modern technologies and use specially equipped greenhouses, which allows them to provide the flower market with quality goods, but there are pitfalls, namely, planting material supplied from the Netherlands, as Ukraine is underdeveloped in terms of the material base for growing flower products). The study shows that customs authorities are particularly concerned about the increase in the volume of falsely declared floral products and the smuggling of flowers. The most common violation detected during the movement of flowers across the customs border is the under-declaration of the weight of imported goods, so the main focus of customs officers is on road checkpoints, where the likelihood of such violations is much higher than on airlines. And every year, new schemes for the illegal movement of flowers are discovered.
Keywords: market; fresh flowers; cut flowers; import; trade; flower business; customs payments; customs clearance; declaration